2012
DOI: 10.1111/j.1440-1797.2012.01622.x
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells are a rescue approach for recovery of deteriorating kidney function

Abstract: Mesenchymal stem cells therapy is a potential therapeutic modality for early phases of CKD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 25 publications
0
22
0
Order By: Relevance
“…Moreover, several studies have indicated that treatment with MSC can ameliorate severe injury to the renal tissues possibly by replenishing tubular epithelial cells [28], mesangial cells [29–31], podocytes [32, 33], and endothelial cells [3437]. Likewise many other studies corroborated the potential of MSC’s in renal tissue regeneration [3848]. These reports suggested that MSCs transplantation can be exploited for replenishing the renal cells.…”
Section: Discussionmentioning
confidence: 93%
“…Moreover, several studies have indicated that treatment with MSC can ameliorate severe injury to the renal tissues possibly by replenishing tubular epithelial cells [28], mesangial cells [29–31], podocytes [32, 33], and endothelial cells [3437]. Likewise many other studies corroborated the potential of MSC’s in renal tissue regeneration [3848]. These reports suggested that MSCs transplantation can be exploited for replenishing the renal cells.…”
Section: Discussionmentioning
confidence: 93%
“…In their study researcher not only showed homing of bone-marrow-derived MSCs but also showed the recovery of kidney in rat model of acute kidney injury [136]. In a pilot clinical study of chronic kidney disease, two intravenous transplantation of ~1 million MSCs/kg body showed significant difference between each of serum creatinine and creatinine clearance levels before and after MSC injection at 1, 3, and 6 months after infusion [137]. …”
Section: Mscs In Different Diseasesmentioning
confidence: 99%
“…Their use was also associated with retarding the occurrence of renal involvement and reducing overall disease activity in SLE80. Stem cells have also been investigated as possible treatment for SLE, especially in severe form of the disease and LN both in mice81 and humans82. In one such study, the use of mesenchyme stem cells, in 10 patients with glomerulonephritis due to SLE, was associated with significant improvement in serum creatinine and creatinine clearance versus control population82.…”
Section: Drugs Used In Treatment Of Lupus Nephritismentioning
confidence: 99%
“…Stem cells have also been investigated as possible treatment for SLE, especially in severe form of the disease and LN both in mice81 and humans82. In one such study, the use of mesenchyme stem cells, in 10 patients with glomerulonephritis due to SLE, was associated with significant improvement in serum creatinine and creatinine clearance versus control population82. The exact mode of benefit of stem cells is not known, but it may be due to differentiation of these cells into renal cells or due to their anti-inflammatory, immunomodulatory, antifibrotic, antiapoptotic, antioxidative, regenerative and paracrine effects83.…”
Section: Drugs Used In Treatment Of Lupus Nephritismentioning
confidence: 99%